VIOLENCE AND POLITICS IN CLANDESTINE PUBLICATIONS UNDER PINOCHET: THE ARMED WORD ON THE PATRIOTIC FRONT MANUEL RODRÍGUEZ. CHILE, 1983-1987 - Pérez Silva, Claudio (Revista de Historia Social y de las Mentalidades, 2011)
This article identifies and characterises, through an análisis of the principal pu- blication of the Frente Patriótico Manuel Rodríguez (FPMR), “El Rodriguista”, the political bases of the political-military strategy of the FPMR and the key elements that configured and guided the daily activities of the rodriguista militarncy during the years, 1983-1987. the article also tries to explain the constitutive elements and the form in which the political homogenisation and identity configuration of the Rodriguista militancy were developed, and which saw the use of political violence as a principal form of ending the military regime.